Controle da qualidade da industrialização do iogurte sem conservante com a aplicação da ferramenta APPCC - Stein, Márcia (2005)
With the purpose of verifying the quality of industrialization of yogurt without artifivcial preservatives with fruit pulp it was decided to use the Analysis of Risks and Critical Control Points, APPCC in SETREM agro industry. The work has started with an APPCC group first constitution were, hen in a second moment established the risks and ways of prevention. Subsequently, the points to be controlled and the points that demonstrate greater risk incidence were determined, the ones called priorities, the critical points of control that the critical limits determined. For the critical limits the control procedures had been established among them the statistics was used carrying out the statistical process control in temperature control during the fermentation of the yogurt where from the superior and inferior limits the control letters were built to follow the process. In order to verify the efficiency of the equipment and operators the application of the Measurement System Analysis (MSA) in ten yogurt samples during the determination of pH-gâmetro. Later wasandyzed necessary corrective actions were delimited to be applied in apply wag lines of the critical limits. Some procedures verification for proper system APPCC were needed, that is, procedures in addition to those used in the control to demonstrate if the system APPCC is being efficient. With the application of the tools, the guarantee of the quality of the final product was gotten decreasing the necessity of the finished product inspections